ANTIPROLIFERATIVE AND APOPTOTIC ACTIVITY OF SULFATED POLYSACCHARIDE ISOLATED FROM HYPNEA VALENTIAE RED SEAWEED IN HUMAN SKIN MALIGNANT MELANOMA CELLS - RAJENDRAN, NEGHA; RAVICHANDRAN, RAMYA; VEERICHETTY, VEERABHUVANESHWARI (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Malignant melanoma is a highly metastatic cutaneous cancer. Deregulated apoptosis has been identified as a major cause of cancer drug resistance. The objective of the study is to evaluate antiproliferative activity of Hypnea Valentiae extract in human skin malignant melanoma (SK-MEL) cells. Methods: In this study, sulfated polysaccharide fraction was precipitated from aqueous extract obtained from H. valentiae. MTT assay was used to determine the cell viability of the crude sulfated polysaccharide against SK-MEL cells and normal L6 cell line (Rat skeletal muscle). Acridine orange (AO) and Ethidium bromide (EB) staining method was applied to study induction of apoptosis in SK-MEL cells. Results: Dose-dependent reduction in cell viability was observed with an IC50 of 30 μg/ml in SK-MEL cancer cells. The sulfated polysaccharide treated SK-MEL cells followed by AO, EB staining, showed typical early apoptotic, and late apoptotic morphological changes. Conclusion: The isolated crude sulfated polysaccharide from H. valentiae produced potent growth inhibition and induction of apoptosis in SK-MEL cells but caused no cytotoxicity in normal L6 skeletal muscle cells.